Saccharomyces cerevisiae as a probiotic agent and a possible aflatoxin B1 adsorbent in simulated fish intestinal tract conditions - Pinheiro, R. E. E. (2020)
The aim of this study was to evaluate in vitro the probiotic potential and absorption of Saccharomyces cerevisiae for the aflatoxin B1 in simulated fish intestinal tract conditions. Three yeast strains were used, two from brewery: S. cerevisiae RC1 and S. cerevisiae RC3 and one from a fish farming environment: S. cerevisiae A8L2. The selected yeasts were subjected to the following in vitro tests: homologous inhibition, self-aggregation, co-aggregation, antibacterial activity, gastrointestinal conditions tolerance and adsorption of AFB1. All S. cerevisiae strains showed good capability of self-aggregation and co-aggregation with pathogenic bacteria. All yeast strains were able to survive the gastrointestinal conditions. In acidic conditions, the factors (strain vs. time) had interaction (P=0.0317), resulting in significant variation among the strains tested in the time periods analyzed. It was observed that there was also interaction (P=0.0062) in intestinal conditions, with an increased number of cells in the 12-hour period for all strains tested. In the adsorption test, the A8L2 strain was statistically more effective (P<0.005) for both AFB1 concentrations evaluated in this study (10 and 25ng/mL). Thus, it was observed that the strains of S. cerevisiae have potential probiotic and adsorbent of AFB1.